Treatment of Blood Blister Aneurysms of the Internal Carotid Artery With Pipeline-Assisted Coil Embolization: A Single-Center Experience - Liu, Peng; Liu, Lunxin; Zhang, Changwei; Lin, Sen; Wang, Ting; Xie, Xiaodong; Zhou, Liangxue; Wang, Chaohua (Frontiers in Neurology, 2022)
Background Blood blister aneurysm (BBA) is a complex and rare aneurysm that presents significant treatment challenges. The application of pipeline embolization device (PED)-assisted coiling in the treatment of ruptured BBA remains controversial. This study aimed to report on our experience and assess the safety and efficacy of this strategy. Methods Between February 2019 and February 2021, 12 patients with ruptured BBAs underwent PED-assisted coil embolization. We collected detailed data about each patient, including demographic information, aneurysmal data, technical details, antiplatelet strategy, operation-related complications, and follow-up outcomes. Results A total of 12 BBA patients were treated with single PED-assisted coil embolization. One patient experienced intraoperative rupture that was controlled by rapid coiling without clinical consequences. All the patients demonstrated complete occlusion on postoperative angiography. A total of three patients had postoperative complications: left hemiparesis, Broca's aphasia, and right hemiplegia due to vasospasm, and transient hemiparesis. Follow-up angiography revealed that all BBAs were completely occluded, except one with neck residue. All patients had favorable outcomes at discharge and the most recent clinical follow-up (mRS score ≤ 2). Conclusion Endovascular treatment of BBAs of the internal carotid artery using PED-assisted coil embolization is a safe and effective strategy. This has contributed to the understanding of BBA therapy and provides a potentially optimal treatment option for this intractable lesion.